Dam haji game using A* search algorithm / Siti Farah Najwa Mukhlis - Mukhlis, Siti Farah Najwa (2017)
This project is about developing a Dam Haji game using A* search algorithm. Dam Haji is an abstract strategy board game which played by two players. It is one of the Malaysia’s Traditional games and it is also known as checkers or draughts in another country. To develop computer games for strategic board game such as chess and checkers, they will used a longer time taken to compute as it involved the pathfinding and searching. Therefore many research have been done to develop this type of computer game by using the Al techniques. In Dam Haji game, the goal is to find the optimal movement to make, so A* algorithm, which is a pathfinding algorithm is used. The project is completed by going through the preliminary study phase, data preparation phase, system design and implementation phase, and the evaluation and result analysis phase. The results of this project is a Dam Haji game using A* algorithm which it is able to make legal movements based on the game’s rules and a matchup with a computer-based player that have gone through a process of computer learning to make movement based on the A* shortest path technique. This project will be evaluated by using the efficiency test and the recommendation for this project in the future is to create count of movements for each player as to use as the win state.